2022
DOI: 10.18176/jiaci.0736
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Nasal Allergen Provocation Test in the Diagnosis of Shellfish Allergy

Abstract: Background: Shellfish allergy is an important cause of food allergy and anaphylaxis worldwide. Several allergenic proteins have been described in the last few years, but the only diagnostic tool that allows discrimination between allergic and non-allergic sensitized subjects is still the oral food challenge (OFC). Objective: The aim of this study was to evaluate the usefulness of nasal allergen provocation test (NAPT) as a diagnostic tool in the diagnosis of shellfish allergy. Methods: Forty-five subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…The allergen used in the nasal provocation test was a lyophilisate of boiled shrimp, and the results were assessed with the help of acoustic rhynometry and a visual analog scale. The results of the study confirmed the usefulness of nasal allergen provocation testing in diagnosing shrimp allergy [23]. In order to diagnose food allergy in our study, apart from the established diagnostic method (DBPCFC) we used an objective method of assessing nasal mucosal reactivity and demonstrated its usefulness and safety.…”
Section: Discussionsupporting
confidence: 75%
“…The allergen used in the nasal provocation test was a lyophilisate of boiled shrimp, and the results were assessed with the help of acoustic rhynometry and a visual analog scale. The results of the study confirmed the usefulness of nasal allergen provocation testing in diagnosing shrimp allergy [23]. In order to diagnose food allergy in our study, apart from the established diagnostic method (DBPCFC) we used an objective method of assessing nasal mucosal reactivity and demonstrated its usefulness and safety.…”
Section: Discussionsupporting
confidence: 75%
“…Boiled shrimp lyophilisate was used for the nasal test and the results were assessed on the basis of acoustic rhinometry and visual analog scale. The results confirmed the usefulness of the nasal allergen provocation test in the diagnostics of shellfish food allergies [19].…”
Section: A B Csupporting
confidence: 73%
“…Our recent report clearly reveals that diagnosis based on clinical history and extract‐based serum‐specific IgE (sIgE) test was poor in differentiating shrimp allergy and tolerance in a cohort of double‐blind placebo‐controlled food challenge (DBPCFC) proven subjects. 6 While nasal allergen provocation test was also shown as a valuable test differentiating sensitized symptomatic shrimp allergic patients from sensitized tolerant subjects, 7 oral food challenges (OFCs) remain the gold standard in diagnosing shrimp allergy.…”
Section: Introductionmentioning
confidence: 99%